O papel dos processos evolutivos e ecológicos nos padrões de diversidade e coloração de espécies - Cerezer, Felipe Osmari (2023)
Naturalists have long recognized the variation of biological diversity over time and space. Two significant aspects that spark great interest in ecology are the latitudinal gradient of diversity and animal coloration. These classic patterns have led to the creation of various historical, evolutionary, and ecological hypotheses, aiming to explain their causes and observed patterns. These two knowledge gaps form the core of my thesis, in which I seek to investigate: 1) the patterns and main causes of latitudinal gradients in species diversity, and 2) the eco-geographic gradients in the coloration of neotropical mammal pelage. In the first chapter, the focus was on the influence of ecosystem productivity and temperature on the diversity and species composition of termites along the latitudinal gradient. The second chapter analyzed three key hypotheses to explain the diversity of groups considered exceptions to the rule, namely those with higher diversity in cold and temperate regions. The third chapter investigated the factors influencing speciation rates in freshwater fish. The fourth chapter examined whether the degree of pigmentation in American marsupials is determined by climatic gradients, as predicted by Gloger's rule. The fifth chapter investigated the geographic variation in coloration of South American rodents, providing new insights into the complex version of Gloger's rule. Collectively, these studies contribute to a better understanding of the patterns and processes that influence biological diversity in different groups of organisms and spatial contexts.